2015
DOI: 10.1002/2015gl064693
|View full text |Cite
|
Sign up to set email alerts
|

MAVEN observations of solar wind hydrogen deposition in the atmosphere of Mars

Abstract: Mars Atmosphere and Volatile EvolutioN mission (MAVEN) observes a tenuous but ubiquitous flux of protons with the same energy as the solar wind in the Martian atmosphere. During high flux intervals, we observe a corresponding negative hydrogen population. The correlation between penetrating and solar wind fluxes, the constant energy, and the lack of a corresponding charged population at intermediate altitudes implicate products of hydrogen energetic neutral atoms from charge exchange between the upstream solar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
133
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(151 citation statements)
references
References 26 publications
8
133
5
Order By: Relevance
“…An energy-dependent charge changing cross section with CO 2 was derived, based on the results of Halekas,Lillis, et al (2015), to determine what fraction of these precipitating ENAs would convert back to penetrating protons. An energy-dependent charge changing cross section with CO 2 was derived, based on the results of Halekas,Lillis, et al (2015), to determine what fraction of these precipitating ENAs would convert back to penetrating protons.…”
Section: Simulations Of Charge Exchange In the Upstream Regionmentioning
confidence: 99%
“…An energy-dependent charge changing cross section with CO 2 was derived, based on the results of Halekas,Lillis, et al (2015), to determine what fraction of these precipitating ENAs would convert back to penetrating protons. An energy-dependent charge changing cross section with CO 2 was derived, based on the results of Halekas,Lillis, et al (2015), to determine what fraction of these precipitating ENAs would convert back to penetrating protons.…”
Section: Simulations Of Charge Exchange In the Upstream Regionmentioning
confidence: 99%
“…Interestingly, the precipitating ion fluxes in the + E hemisphere are slightly stronger than those in the − E hemisphere around the nightside polar region for the latitude higher than ∼50° with the local time of 21–3 h. While the strong precipitating ion fluxes are generally observed in the dayside subsolar region ( 40°) in both the ± E hemispheres, the precipitating ion fluxes are typically stronger in the + E hemisphere rather than in the − E hemisphere (blue bins at low‐latitude dayside in Figure c). These precipitating ion populations might be partially responsible for the penetrating double‐charge exchange protons seen in the Martian upper atmosphere [ Halekas et al , , ], rather than heavy ions; however, it has never been reported that these penetrating protons display an asymmetric distribution between the ± E hemispheres. A discussion of what ion species may be responsible for the hemispheric asymmetry of the ion precipitation in the MSE coordinates is left in section 4, where we investigate different precipitation maps for protons and heavy ions.…”
Section: Swia Observations Of Precipitating Ions In the Mse Coordinatesmentioning
confidence: 99%
“…A portion of the solar wind protons charge exchange with the Martian exospheric constituents, resulting in energetic neutral atoms (ENAs) and allowing them to penetrate to low altitudes in the atmosphere, because they do not feel the ambient electromagnetic fields. Some of these ENAs can be converted back to charged particles that can be measured by SWIA around the MAVEN closest approach [ Halekas et al , , ]. Since these ENAs can penetrate to low altitudes, maintaining the same velocity as that of solar wind, the penetrating protons velocity (Figure b) is the most reliable proxy to determine the upstream solar wind velocity.…”
Section: Dependence On Upstream Solar Wind Driversmentioning
confidence: 99%